2004
DOI: 10.1016/j.accreview.2004.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Risk of decompression illness among 230 divers in relation to the presence and size of patent foramen ovale

Abstract: Background The risk of developing decompression illness (DCI) in divers with a patent foramen ovale (PFO) has not been directly determined so far; neither has it been assessed in relation to the PFO's size. Methods In 230 scuba divers (age 39 ± 8 years), contrast trans-oesophageal echocardiography (TEE) was performed for the detection and size grading (0-3) of PFO. Prior to TEE, the study individuals answered a detailed questionnaire about their health status and about their diving habits and accidents. For in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…A recent study found a strong relationship between PFO size and DCS in a study of 230 divers (6). Another study demonstrated the functional and anatomic characteristics of PFO with and without DCS (7).…”
Section: Pfo: Associated Clinical Syndromesmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent study found a strong relationship between PFO size and DCS in a study of 230 divers (6). Another study demonstrated the functional and anatomic characteristics of PFO with and without DCS (7).…”
Section: Pfo: Associated Clinical Syndromesmentioning
confidence: 97%
“…It is a risk factor for several serious clinical syndromes, including paradoxic systemic embolism, such as ischemic stroke (3), myocardial infarction (4), decompression sickness (DCS) in divers (5)(6)(7), and complications of pulmonary embolism (8). Recent evidence further implicates PFO as a possible cause of migraine headache through mechanisms not yet understood.…”
mentioning
confidence: 98%
“…In this case, the diver must be strongly advised of the risk in continuing scuba practice, regardless of the presence of a previous DS event, and he/she should consider percutaneous transcatheter closure of the PFO to allow safer scuba activity. On another hand, the finding by Torti et al [68] that a small PFO behaves like no PFO regarding the frequency of serious DS renders the recommendation, in this case, less strict for refraining from diving.…”
Section: Pfo and Decompression Sickness (Dcs)mentioning
confidence: 85%
“…However, PFO has been found to be implicated; e.g., in cryptogenic stroke [16], decompression illness [17], and perhaps migraine with aura [18].…”
Section: Significance Of Pfomentioning
confidence: 99%
“…PFO has been found to increase the risk of major decompression illness five times from one to five in 10,000 dives and the risk increases with increasing PFO size [17]. The current European clinical fitness to diving practice does not, however, include PFO screening before diving, as the absolute risk is very low and most patients recover completely after recompression treatment [60].…”
Section: Decompression Illnessmentioning
confidence: 99%